The Gut Microbiome of Preterm Infants Treated With Aminophylline Is Closely Related to the Occurrence of Feeding Intolerance and the Weight Gain - Shen, Wei; Qiu, Wen; Lin, Qi; Zeng, Chao; Liu, Yuting; Huang, Weimin; Zhou, Hongwei (Frontiers in Nutrition, 2022)
Background: Aminophylline is widely used in the treatment of preterm infants, but it can cause feeding intolerance events, in which gut microbial dysbiosis may have a role. This study aims to investigate the relationship between the gut microbiome of preterm infants treated with aminophylline and the occurrence of feeding intolerance and weight gain rate. Methods: This study included a cohort of 118 preterm infants. Survival analysis and multivariate Cox regression were used to evaluate the relationship between aminophylline treatment and the occurrence of feeding intolerance. 16S rRNA V4 region gene sequencing was used to characterize the microbiome of fecal samples from the cohort. Linear discriminant analysis effect size was used to analyze the differential abundance of bacteria related to aminophylline treatment. Wilcoxon test, Kruskal–Wallis test, Spearman correlation coefficients and generalized linear mixed models were used to analyze the correlation between the differential bacteria and feeding intolerance events as well as the weight gain. Results: The results showed that the use of aminophylline could significantly increase the occurrence of feeding intolerance. The relative abundances of Streptococcus and Rothia in the gut microbiome of preterm infants were positively correlated with both the occurrence of feeding intolerance and the use of aminophylline, while the relative abundance of Staphylococcus was negatively correlated. In particular, preterm infants with a lower relative abundance of Rothia were more likely to develop feeding intolerance associated with aminophylline, and this difference existed before the onset of feeding intolerance. Moreover, it took longer for individuals with a lower relative abundance of Streptococcus to reach 2 kg weight. The contribution of Streptococcus to weight gain was greater than that of Bifidobacterium or Lactobacillus. Conclusion: The gut microbiome in preterm infants treated with aminophylline was characterized by a decrease in Streptococcus and Rothia and an increase in Staphylococcus. These microbes, especially Rothia, were positively correlated with the occurrence of feeding intolerance. Streptococcus but not Bifidobacter likely participated in the weight gain of preterm infants in early life.